G‐protein‐coupled receptor kinase 2 safeguards epithelial phenotype in head and neck squamous cell carcinomas. Issue 1 (7th January 2020) - Palacios‐García, Julia; Sanz‐Flores, María; Asensio, Alejandro; Alvarado, Raúl; Rojo‐Berciano, Susana; Stamatakis, Konstantinos; Paramio, Jesús M.; Cano, Amparo; Nieto, M. Ángela; García‐Escudero, Ramón; Mayor, Federico; Ribas, Catalina
Abstract : Head and neck squamous cell carcinoma (HNSCC) arises from the mucosal lining of the upper aerodigestive tract and display few treatment options in advanced stages. Despite increased knowledge of HNSCC molecular biology, the identification of new players involved in triggering HNSCC recurrence and metastatic disease is needed. We uncover that G‐protein‐coupled receptor kinase‐2 (GRK2) expression is reduced in undifferentiated, high‐grade human HNSCC tumors, whereas its silencing in model human HNSCC cells is sufficient to trigger epithelial‐to‐mesenchymal transition (EMT) phenotypic features, an EMT‐like transcriptional program and enhanced lymph node colonization from orthotopic tongue tumors in mice. Conversely, enhancing GRK2 expression counteracts mesenchymal cells traits by mechanisms involving phosphorylation and decreased functionality of the key EMT inducer Snail1. Our results suggest that GRK2 safeguards the epithelial phenotype, whereas its downregulation contributes to the activation of EMT programs in HNSCC. Abstract : What's new? Head and neck squamous cell carcinoma (HNSCC) recurs in more than half of patients, with most ultimately dying from metastatic disease. In order to reverse this trend, a better understanding of molecular alterations that contribute to HNSCC is needed. Here, the authors identify a link between G‐protein‐coupled receptor kinase 2 (GRK2), a key signaling hub, and HNSCC, whereby high‐grade HNSCC tumors were found to exhibit atypically low GRK2 levels. Experiments in HNSCC cells further revealed that GRK2 silencing triggers epithelial‐to‐mesenchymal transition features, suggesting that GRK2 serves a key role in preserving the differentiated epithelial phenotype of squamous cells.